A new temperature parameter set for characterizing the frictional temperature rise of disc brakes. Issue 1 (8th February 2016) - Yin, Yan; Xiao, Xingming; Bao, Jiusheng; Liu, Jinge; Lu, Yuhao; Ji, Yangyang
Abstract : Purpose: – The purpose of this study is to establish a new temperature set for characterizing the frictional temperature rise (FTR) of disc brakes. The FTR produced by braking is an important factor which directly affects the tribological properties of disc brakes. Presently, most existing researches characterize the FTR only by several static parameters such as average temperature or maximum temperature, which cannot reflect accurately the dynamic characteristics of temperature variation in the process of braking. In this paper, a new temperature parameter set was extracted and the influences of braking conditions on these parameters were investigated by experiments. Design/methodology/approach: – First, several simulated braking experiments of disc brakes were conducted to reveal the dynamic variation rules and mechanisms of the FTR in braking. Second, the characteristic parameter subset of the FTR was extracted with five significant parameters, namely, initial temperature, average temperature, end temperature, maximum temperature and the ratio of maximum temperature time. Furthermore, the fitting parameter subset of the FTR was constructed based on the temperature rise curve. Finally, the influence and mechanisms of initial braking velocity and braking pressure on the new temperature parameter set were investigated through braking experiments. Findings: – This paper extracted a new temperature parameter set including a characteristic parameter subset and a fitting parameter subset and revealed the influences of braking conditions on it by experiments. Originality/value: – The results showed that the new temperature parameter set extracted in this paper can characterize the dynamic characteristics of disc brake's FTR variations more objectively and comprehensively. The research results will provide a theoretical basis for extracting the fault feature of friction properties.